2006
DOI: 10.1115/1.2356866
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Data Center Room Layout to Minimize Rack Inlet Air Temperature

Abstract: In a typical raised floor data center with alternating hot and cold aisles, air enters the front of each rack over the entire height of the rack. Since the heat loads of data processing equipment continue to increase at a rapid rate, it is a challenge to maintain the temperature of all the racks within the stated requirement. A facility manager has discretion in deciding the data center room layout, but a wrong decision will eventually lead to equipment failure. There are many complex decisions to be made earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The cold air supply in the data center involves the interaction of high quality flow rates with complex thermal fluids [14]. The governing equations of fluid flow describing the property fields can be written as follows:…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cold air supply in the data center involves the interaction of high quality flow rates with complex thermal fluids [14]. The governing equations of fluid flow describing the property fields can be written as follows:…”
Section: Simulation Methodsmentioning
confidence: 99%
“…They believed that the supply/return air location was an important factor in high-density data centers. Sammakia et.al [14,15] found that some adjustment methods, such as minimizing local hot spots in the data center, affected the air inlet temperatures, which was one of the keys to effective thermal management. These studies took the approach of optimizing the data center layouts and cooling system schemes to achieve energy efficiency and maintain the indoor temperature within the recommended limits [16].…”
Section: Of 14mentioning
confidence: 99%
“…Researchers have explored airflow distribution optimization, including the optimization of air supply and return form [7,[26][27][28][29], both optimization and adjustment of equipment layout in the computer room [30][31][32][33][34], and studies on the influence of air flow characteristics under raised floor [35][36][37][38][39].…”
Section: Airflow Distributionmentioning
confidence: 99%
“…The influence study on characteristics of air flow under raised floor refers to the analyzed the uniformity of the thermal environment of the raised floor air supply computer room. Bhopte [36] et al discussed the effect of plenum depth, floor tile placement, and ceiling height on the rack inlet air temperature in a raised floor data center with 12 kW racks. And a multivariable approach to optimize data center room layout to minimize the rack inlet air temperature is proposed.…”
Section: Airflow Distributionmentioning
confidence: 99%
“…During this period, the thermal community responded with several initiatives that improved TIMs [32,33,34,35], thermal metrology [36,37], modelling [38,39] and various building block technologies such as microchannel heatsinks [40,41,42,43,44], ionic wind [45], heat pipes [46,47], and thermoelectric coolers [48,49]. It also saw the emergence of major research efforts funded in the US by DARPA programs such as HERETIC (starting 1992), followed by nTIM, MACE, TGP, NJTT, and ACM (2008), and most recently by the Intra/Interchip Enhanced Cooling (ICECool) program (2012).…”
Section: B Thermal and Electrical Challengesmentioning
confidence: 99%